AN ANALYSIS OF STUDENTS’ ERRORS IN USING POSSESSIVE ADJECTIVES IN THEIR WRITING TASKS - Rizal Pratama Firdaus (Universitas Galuh, 2022)
This study is purposed to analyze 1) the kinds of possessive adjective errors which are mostly made by students in their writing tasks; and 2) the causes of possessive adjective errors which are mostly made by students in their writing tasks. A case study is used as a research design which engaged the students at the tenth grade of a vocational school in Singaparna, Tasikmalaya. By means of purposeful sampling technique, 17 students at class X-TKR 1 are selected as the participants of this study. This study uses two instruments namely, the students’ worksheet on writing test and the semi-structured interview. The result shows that ‘his’ and ‘her’ were the kinds of possessive adjective errors which are mostly made by students in their writing tasks. The results also presented that the students make errors in using and in writing possessive adjectives because they are not aware of possessive adjectives, their grammar is still poor which lead to boredom, unmotivated, and uninterested in learning. The strategies or ways applied by the students are effective to overcome their errors in using and in writing possessive adjectives in their writing tasks so that they are able to identify their errors and difficulties, to correct their errors, and to be focus in learning grammar, especially in learning possessive adjectives